Manipulating Electrical and Fluidic Access in Integrated Nanopore‐Microfluidic Arrays Using Microvalves. Issue 10 (27th December 2016) - Tahvildari, Radin; Beamish, Eric; Briggs, Kyle; Chagnon‐Lessard, Sophie; Sohi, Ali Najafi; Han, Shuo; Watts, Benjamin; Tabard‐Cossa, Vincent; Godin, Michel
Abstract : On‐chip microvalves regulate electrical and fluidic access to an array of nanopores integrated within microfluidic networks. This configuration allows for on‐chip sequestration of biomolecular samples in various flow channels and analysis by independent nanopores.